The impact of anxiety on postural control: CO2 challenge model. (6th October 2022) - Taylor, Alexander N. W.; Low, Daniel C.; Walsh, Gregory S.; Holt, Nigel
Abstract: Anxiety and balance and postural control are linked via common neural pathways, such as the parabrachial nucleus network. A laboratory‐based model of general anxiety disorder (GAD) using the CO2 challenge, has potential to be used to observe this relationship, potentially mimicking subjective, autonomic, and neuropsychological features of GAD. The current feasibility study used the CO2 challenge to explore postural control changes in healthy adults. It was predicted that during the CO2 condition, participants would show increased postural sway path length and decreased sway stability, compared with a normal air breathing condition. To assess this, heart and breathing rate, quiet standing postural sway path length, sway dynamic stability, and subjective measures of emotion were measured either before and after or during and after the inhalation conditions. Results demonstrated that CO2 inhalation led to both an increase in sway path length and reduced sway stability compared to the air breathing conditions; the effect on sway path lasted after the inhalation of CO2 had ceased. Additionally, replication of HR and subjective measures of emotion were observed when comparing air and CO2 conditions. This provides experimental evidence that CO2 inhalation can affect balance, suggestive of shared mechanisms between anxiety and balance performance, as well as indicating that the CO2 model of GAD is suitable to look at changes in balance performance in healthy adults. Future use of this model to explore factors that can reduce the influence of GAD on balance would be beneficial as would a more detailed exploration of the neural pathways associated with the associated comorbidity. Abstract : This feasibility study demonstrates the potential of using the CO2 challenge model as an experimental tool to better understand the relationship between anxiety and balance disorders. We evidenced increased path sway and stability as the result of 7.5% CO2 inhalation induced anxiety state. Furthermore, increased heart rate and poorer self‐reported mood state due to the CO2 inhalation, corroborate previous findings of generalised anxiety disorder symptomology in this model.